2021
DOI: 10.1002/jev2.12094
|View full text |Cite
|
Sign up to set email alerts
|

First‐in‐human intracochlear application of human stromal cell‐derived extracellular vesicles

Abstract: Extracellular vesicles (EVs) derived from the secretome of human mesenchymal stromal cells (MSC) contain numerous factors that are known to exert anti‐inflammatory effects. MSC‐EVs may serve as promising cell‐based therapeutics for the inner ear to attenuate inflammation‐based side effects from cochlear implantation which represents an unmet clinical need. In an individual treatment performed on a ‘named patient basis’, we intraoperatively applied allogeneic umbilical cord‐derived MSC‐EVs (UC‐MSC‐EVs) produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 47 publications
2
41
0
Order By: Relevance
“…However, recent studies indicate that the circulating extracellular vesicles from young serum could rejuvenate aged cell bioenergetics to promote brain and skeletal muscle regeneration in aging animals, opening the possibility of treating degenerative diseases using novel exosome-based therapies [ 99 , 100 ]. In addition to its extraordinary therapeutic effect, exosome-based therapy also shows the advantages of a high feasibility of clinical translation; indeed, the first-in-human application of MSC-derived EVs was recently reported in Australia [ 101 ]. Considering the non-invasive properties of injection, as well as the biocompatibility of exosomes, injectable hydrogels with loaded exosomes or exosomes with small molecular drugs hold promise to manage OA and IVDD prior to patients reaching the advanced stage of disease in the future.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…However, recent studies indicate that the circulating extracellular vesicles from young serum could rejuvenate aged cell bioenergetics to promote brain and skeletal muscle regeneration in aging animals, opening the possibility of treating degenerative diseases using novel exosome-based therapies [ 99 , 100 ]. In addition to its extraordinary therapeutic effect, exosome-based therapy also shows the advantages of a high feasibility of clinical translation; indeed, the first-in-human application of MSC-derived EVs was recently reported in Australia [ 101 ]. Considering the non-invasive properties of injection, as well as the biocompatibility of exosomes, injectable hydrogels with loaded exosomes or exosomes with small molecular drugs hold promise to manage OA and IVDD prior to patients reaching the advanced stage of disease in the future.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Warnecke et al [ 107 ] reported a first-in-human case study that utilized MSC-EVs derived from umbilical cord tissues to reduce inflammation during cochlear implantation. Briefly, the authors obtained 1.03 × 10 11 particles/mL of EVs with a diameter range of 110–130 nm, as measured by nanoparticle tracking analysis, via a combination of tangential flow filtration (TFF) and diafiltration techniques post culture.…”
Section: Sevs and The Treatment Of Liver Diseasesmentioning
confidence: 99%
“…This showed that MSCs-derived exosomes may find successful application in clinical use. Furthermore, improvements in the methods that can reduce the quantity of exosomes needed for efficient treatment will further expedite their use in clinical scenarios[ 107 ].…”
Section: Sevs and The Treatment Of Liver Diseasesmentioning
confidence: 99%
“…Applications for tissue repair are under intense scrutiny, with substantial improvements in cardiac, cutaneous, lung, bone, and joint injuries. MSC-derived EVs remain at the forefront of these studies [7,8,27], but other cells seem promising [28,29]. From a product development and regulatory perspective, using native EVs originating from unmodified cells may be the most manageable situation, as developed in Section 3.…”
Section: Evs From Native Unmodified Cellsmentioning
confidence: 99%